The Integration of Day Light with Advance Fuzzy Based Controllers for Institutional Buildings in the Region of Central Queensland, Australia. (May 2017) - Ghadi, Yazeed Yasin; Rasul, M.G.; Khan, M.M.K.
Abstract: Smart buildings lately have gained momentum due to its ability to drive, manage and control energy conservation measures. Fuzzy based controllers in Building Management Systems (BEMS) can use the latest and the most innovative control strategies in order to achieve a comfortable life style while savings energy and reducing greenhouse gas emissions. This system uses real life events as a point of control. Those real life events may include day-light usage (natural light), occupancy profile, passive cooling techniques and the usage of ambient atmosphere based on its ambient temperature and humidity. This paper develops a BMS using advanced fuzzy based controllers with integration of day light. This control strategy is based on quantifying the outside and the inside illuminance and allowing an add-on controller to perform a photometric calculation and comparison to decide rooms openings (windows). The paper also analyses energy savings and recommend suitable markets for this control strategy either during the design stage of a building, or after the building construction or retrofitting.